Advances and mechanisms in polymer composites toward thermal conduction and electromagnetic wave absorption - Guo, Yongqiang; Ruan, Kunpeng; Wang, Guangsheng; Gu, Junwei (Science bulletin, 2023)
Typical application forms of thermal conduction and EMW absorption integrated polymer composites. [Display omitted] Polymer composites have essential applications in electronics due to their versatility, stable performance, and processability. However, with the increasing miniaturization and high power of electronics in the 5G era, there are significant challenges related to heat accumulation and electromagnetic wave (EMW) radiation in narrow spaces. Traditional solutions involve using either thermally conductive or EMW absorbing polymer composites, but these fail to meet the demand for multi-functional integrated materials in electronics. Therefore, designing thermal conduction and EMW absorption integrated polymer composites has become essential to solve the problems of heat accumulation and electromagnetic pollution in electronics and adapt to its development trend. Researchers have developed different approaches to fabricate thermal conduction and EMW absorption integrated polymer composites, including integrating functional fillers with both thermal conduction and EMW absorption functions and innovating processing methods. This review summarizes the latest research progress, factors that affect performance, and the mechanisms of thermal conduction and EMW absorption integrated polymer composites. The review also discusses problems that limit the development of these composites and potential solutions and development directions. The aim of this review is to provide references for the development of thermal conduction and EMW absorption integrated polymer composites.